Intradisciplinarity: can one theory do it all? - Martin, J. R. (Frontiers in Communication, 2024)
This position paper draws on Bernstein and Maton's sociology of knowledge to explore Systemic Functional Linguistics (SFL) and Systemic Functional Semiotics (SFS), alongside their relation to Bateman's vision for empirical multimodality research. The paper suggests that SFL/SFS's internal grammar is by and large compatible with Bateman's vision, even if its external grammars fall short insofar as extant descriptions of one semiotic system or another are concerned. The paper closes with the suggestion that SFS and Bateman's multimodality can learn most from one another in research projects embracing a dialectic of theory, description and ideologically committed practice.